Optimizing contract document management: A case study of the legal and compliance unit at PTAPI - Pertiwi, Ni Kadek Wanda Maheswari; Lasmini, Ni Ketut; Wajdi, Majid; Ghimire, Shiva Raj (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2025)
This study investigates the procedures for managing contract documents at the Legal & Compliance Unit of PTAPI. The objective is to examine the existing workflow related to the handling and archiving of agreement documents and to identify key challenges, especially concerning the retrieval of signed contracts by business partners. Employing a descriptive qualitative research method, data were collected through direct observation, in-depth interviews with legal staff, and a thorough review of institutional documentation. The research findings reveal that while the unit processes more than 300 contract agreements annually, there is no formalized procedure regulating the timeline for business partners to collect their signed documents. This has resulted in the accumulation of uncollected contracts, physical storage congestion, increased administrative burdens, and reduced staff productivity. Key contributing factors include the absence of an internal standard operating procedure (SOP), lack of enforcement policies or sanctions for delays, limited digital document archiving, and inadequate communication or notification systems directed at partners. The study emphasizes the urgent need for establishing standardized document retrieval protocols, implementing structured deadlines for collection, automating partner notifications, and investing in digital documentation systems. By adopting these strategies, the Legal & Compliance Unit can enhance its administrative efficiency, reduce legal risks, and improve overall service quality. Furthermore, the results offer valuable insights and practical policy recommendations that can be adapted by similar units in other corporate or public-sector environments seeking to improve contract lifecycle management.